Innovation technology : A dictionary (2017)
The term “innovation” comes from the Greek word kainotomia, which is derived from kainos, or “new,” and seems to date back to the 5th-century BCE [1]. The term seems to have originally referred to new thoughts, sometimes with a neutral or positive connotation, but more often with a negative connotation [1]. Godin [1, 2] distinguishes between two episteme, 1 within which the term “innovation” has been understood and used quite differently. In the early modern episteme, which held from the 1500s through to the 1800s, innovation meant “introducing novel change,” particularly with regard to religious and/or political change. In those early times, the term “innovation” seems to have quickly taken on a negative, perjorative connotation. It was frequently meant to imply that the changes were unwanted, unnatural (apart from the natural order of things), revolutionary, and/or dangerous, as in “introducing change into the established order” [1]. In this era, whether in the context of politics or religion, introducing changes (innovation), was the purview of the political and religious leaders only. In contrast, the terms “reformation” or “restoration” were frequently used to describe positive, moderate, natural-order-restoring changes.